MANAJEMEN LABA DENGAN MOTIVASI PAJAK PADA BADAN USAHA MANUFAKTUR DI INDONESIA - Setiadi Alim (University of Merdeka Malang, 2009)
This research investigated whether accounting earnings of manufacture corporations listedon Indonesia Capital Market were managed decreasing in response to Income Tax Reform Actof 2008. To fi nd income decreasing, earning management evidence would used total accruals Jonesmodifi cation model (Dechow et al., 1995). Total accruals would be classifi ed to discretionary accrualsand non discretionary accruals. Our empirical tests found signifi cantly negative discretionary accrualsin 2008. This result showed that there was income decreasing earning management in fi nancial statement2008 of manufacture corporations listed on Indonesia Capital Market. Our study also found thatthis negative discretionary accruals were negatively associated with levels of debt, but there was norelation with corporates size.